TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPALS AT MTS NEGERI TOJO UNA-UNA AND IMPACT ON IMPROVING THE QUALITY OF HUMAN RESOURCES - Suci Indasari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to analyze the transformational leadership style of school principals at MTs Negeri Tojo Una-Una and its impact on improving the quality of human resources. Using a qualitative approach, this research involved interviews, observation, and documentation as data collection methods. The research results show that school principals actively improve the quality of teachers and students through support for each school community, from an internal perspective (morale by providing various role models and advice), as well as externally (training, providing school facilities, collaboration between the community and government). Good leadership, exemplary behavior, and communication that creates a conducive school environment are some of the key factors in creating a comfortable and enjoyable school environment which is proven to increase motivation and involvement of all parties in the learning process, from cooperation and collaboration in every activity. These findings emphasize the importance of transformational leadership in achieving the vision and mission of better education with optimal-quality human resources.